Decree of the Prime Minister No. 38 of the year 2019 On Amending Certain Provisions of the Executive Regulations of Books One, Two and Four of the Law on Protection of Intellectual Property Rights As Issued by the Prime Minister Decree No. 1366 of the Year 2003 = قرار مجلس الوزراء رقم 38 لسنة 2019 بتعديل بعض أحكام اللائحة التنفيذية للكتب الأول والثانى والرابع من قانون حماية حقوق الملكية الفكرية الصادرة بقرار رئيس مجلس الوزراء رقم 1366 لسنة 2003 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic